2014
DOI: 10.1103/physreva.90.042301
|View full text |Cite
|
Sign up to set email alerts
|

Toward high-dimensional-state quantum memory in a cold atomic ensemble

Abstract: Quantum memories have been realized in different physical systems, such as atomic ensembles or solid systems. To date, all quantum memories have realized the storage and retrieval of photons encoded using only a two-dimensional space spanned, for example, by the orthogonal polarization states, and hence can only store a quantum bit. Using electromagnetically induced transparency in a cold atomic ensemble, we report the experimental realization of a quantum memory storing a photon encoded in a three-dimensional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Before verifying the high-dimensional entanglement, the correlations in the OAM space between the two ensembles before and after storage were first measured. The results are shown in 2(a)]; this is similar to the result that was obtained when using a weak coherent light [6]. The different storage efficiencies measured for different OAM modes m are shown in Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Before verifying the high-dimensional entanglement, the correlations in the OAM space between the two ensembles before and after storage were first measured. The results are shown in 2(a)]; this is similar to the result that was obtained when using a weak coherent light [6]. The different storage efficiencies measured for different OAM modes m are shown in Fig.…”
Section: Resultssupporting
confidence: 81%
“…Next, we verified the entanglement with d=3. We projected the signal-1 and signal-2 photons onto SLM 1 and SLM 2, respectively, with nine different phase states |ψ 19 > corresponding to states |L>, |G>, |R>, (|G>+|L>)/2 1/2 , (|G>+|R>)/2 1/2 , (|G>+i|L>)/2 1/2 , (|G>-i|R>)/2 1/2 , (|L>+|R>)/2 1/2 , and (|L>+i|R>)/2 1/2 [6,32], where |L>, |G>, and |R> are states corresponding to a well-defined OAM of −ћ, 0, and +ћ, respectively. With this projection, the mirrors and lens should be considered due to the photon's transformation during the imaging process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this work is a proof of principle, it makes an important step toward realizing high-dimensional quantum memory. In 2014, this research group reported a demonstration of quantum memory storing a photon encoded in a three-dimensional space 43 . In 2015, Zhou et al .…”
Section: Methodsmentioning
confidence: 99%
“…Pioneering works of quantum memories with high dimension states have been demonstrated in both crystal 6,[9][10][11] and atomic ensemble 12,13 by using angular modes, 14 spatial modes, 15 time-bin modes, 16 and OAM modes. 12 Among these proposals, the OAM mode with infinite-dimensional spanning in Hilbert space makes it an excellent candidate for high dimensional quantum memories.…”
Section: Introductionmentioning
confidence: 99%